Reducing Pain Due to Vaccination: Comparison of Distraction and Oral Sucrose - Kheirkah M. MSc; Hadadi Moghadam. H MSc; Jamshidi Manesh. M MSc; Haghani. H MSc (Iran University of Medical Sciences, 2011)
Background and Aim: Neonates ' reaction to pain is more severe than adults. Therefore, recognition and application of pain control strategies by health care workers is necessary. Immunization is a common painful event during infancy, which is typically performed without pain control. The aim of this study was to examine the effect of distraction technique and oral sucrose on reducing vaccination pain.   Material and Methods: this randomized clinical trial was performed on healthy infants referring to the health centers of Tehran University of Medical Sciences in west of Tehran by their mother for DPT technique vaccination. Healthy infants groups (n=114) were randomly assigned to distraction (n=38), oral sucrose (n=38) and routine care (n= 38) groups. Infants in distraction group, were provided with a (rattle), 30 seconds before, during, and 15 seconds after the injection. Infants in sucrose group received 2 ml oral sucrose 2 minutes before injection and the control group received routine care (just lying on examination table). Pain symptoms were measured by Modified Behavioral Pain Scale (MBPS) during 5 seconds before to 15 seconds after vaccination. Descriptive and inferential statistics (independent T-test) were used to analyze data using SPSS-PC.   Results : MBPS scores in distraction group and sucrose group were significantly lower than the control group (P= 0.0001). No significant difference was seen between oral sucrose group and distraction group (P= 0.581).   Conclusion: Distraction technique and oral sucrose are recommended as easy to use, inexpensive and effective measures for immunization pain management of neonates